Effect of Bleaching Gels on Surface Roughness of Nanofilled Composite Resins - Wang, Linda; Francisconi, Luciana Fávaro; Atta, Maria Teresa; Santos, Jean Rodrigo dos; Padre, Natália Coelho Del; Gonini-Júnior, Alcides; Fernandes, Karen Barros Parron (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to investigate the superficial texture of composite restorations after different bleaching protocols. Methods: Filtek Supreme (S), Filtek Z350 (F), and Grandio (G) were compared to Opallis (O) and Filtek Z250 (Z) (control microhybrid composites) and to bovine enamel using three different bleaching agents: 35% hydrogen peroxide Whiteness HP (WHP), 35% Whiteness HP MAXX (WMAXX) and 16% carbamide peroxide Whiteness Standard (WS). Six specimens from each composite were treated using each bleaching agent, according to the manufacturers’ instructions. Three random sites were measured for superficial roughness (Hommel Tester T 1000) weekly for each sample. Data were analyzed for each bleaching system using two-way ANOVA and Bonferroni tests at 5% significance level. Results: WHP treatment significantly altered the Filtek Supreme composite over time. When WMAXX was used, Grandio displayed the most significant alterations in surface roughness throughout the evaluation period, which was not observed for the other nanocomposites. Using WS, Filtek Z250 presented significant surface alterations over time, which was not seen in the nanofilled materials. Conclusions: Surface roughness alteration was material and time-dependent. The bleaching gels affected nanofilled and microhybrid composite resins. Enamel was the surface less affected by bleaching. (Eur J Dent 2011;5:173-179)
Keywords: Tooth bleaching; Nanotechnology; Resin composites; Surface roughness